2017
DOI: 10.1186/s12934-017-0805-7
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic modeling of Shewanella baltica KB30 growth on different substrates through respirometry

Abstract: Background Shewanella baltica KB30 was isolated from seawater collected in Kandalaksha Bay, White Sea (Russia). This strain is known for its ability to grow on a pool of different substrates, including carbohydrates, carboxylic and amino acids, and lipids. However, no data are available on its metabolic efficiency in relation to the use of different carbon sources typologies. This work represents the first attempt to characterize S. baltica by its heterotrophic kinetic performance.ResultsGrowth and substrate c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 28 publications
(46 reference statements)
0
7
0
Order By: Relevance
“…alvei is an ideal resistant-isolate candidate in any system. These traits can also be found in species of Shewanella [ 68 , 69 ], Serratia [ 70 , 71 ], Carnobacterium [ 72 ], Brochotrhix [ 73 , 74 ], and Kluyvera [ 75 , 76 ]. All of these bacteria can colonize multiple environments, and the ability to acquire resistance in any given environment represents a significant risk for human health.…”
Section: Discussionmentioning
confidence: 99%
“…alvei is an ideal resistant-isolate candidate in any system. These traits can also be found in species of Shewanella [ 68 , 69 ], Serratia [ 70 , 71 ], Carnobacterium [ 72 ], Brochotrhix [ 73 , 74 ], and Kluyvera [ 75 , 76 ]. All of these bacteria can colonize multiple environments, and the ability to acquire resistance in any given environment represents a significant risk for human health.…”
Section: Discussionmentioning
confidence: 99%
“…Since the yield coefficient can be calculated, the following relation can give an estimation of the growth rate for the biomass: rX=μX=Yritalicsu where X is the concentration of active biomass in the sample. Thus, solving μ=YritalicsuX following the Monod growth model, the growth rate is related to a maximum growth rate μ max and a saturation constant K S : μ=YritalicsuX=μitalicmaxSKS+S If we were to linearize Eqn (5): 1μ=KSμmax1S+1μmax …”
Section: Methodsmentioning
confidence: 99%
“…following the Monod growth model, 29 the growth rate is related to a maximum growth rate max and a saturation constant K S :…”
Section: Kinetic Characterization Of Biomassmentioning
confidence: 99%
“…However, a fermentative metabolism could explain the selection of Shewanella over Geobacter in our enrichments and in all incubation conditions, because this genus can grow either using fermentation or Fe(III) reduction (Bowman, 2015). Moreover, Leyva-Díaz et al (2017) showed that peptone was a better substrate for the growth of Shewanella baltica than glucose or acetate. As our medium contained 1.5 g L −1 peptone, this substrate could also favor the growth of bacteria belonging to the Shewanella genus.…”
Section: Geobacter and Shewanella 16s Genes Abundancesmentioning
confidence: 99%